The Gaia-ESO Survey: evidence of atomic diffusion in M67?. Issue 1 (24th April 2018) - Bertelli Motta, C; Pasquali, A; Richer, J; Michaud, G; Salaris, M; Bragaglia, A; Magrini, L; Randich, S; Grebel, E K; Adibekyan, V; Blanco-Cuaresma, S; Drazdauskas, A; et al.
ABSTRACT: Investigating the chemical homogeneity of stars born from the same molecular cloud at virtually the same time is very important for our understanding of the chemical enrichment of the interstellar medium and with it the chemical evolution of the Galaxy. One major cause of inhomogeneities in the abundances of open clusters is stellar evolution of the cluster members. In this work, we investigate variations in the surface chemical composition of member stars of the old open cluster M67 as a possible consequence of atomic diffusion effects taking place during the main-sequence phase. The abundances used are obtained from high-resolution UVES/FLAMES spectra within the framework of the Gaia-ESO Survey. We find that the surface abundances of stars on the main sequence decrease with increasing mass reaching a minimum at the turn-off. After deepening of the convective envelope in subgiant branch stars, the initial surface abundances are restored. We found the measured abundances to be consistent with the predictions of stellar evolutionary models for a cluster with the age and metallicity of M67. Our findings indicate that atomic diffusion poses a non-negligible constraint on the achievable precision of chemical tagging methods.